ETNOGRAFI SENI PERTUNJUKAN RITUAL DI KABUPATEN SUMEDANG - Dede Suryamah (Paraguna, 2016)
This article  is  an  ethnographic stud  that explores   the  phenomenon of performing arts which functioned as a means  of rituals in the society.  The assumption ocused  in this paper is  the social fact  that the inception of a culture    work  in  society   can   not   be  separated   from   the   historical background of the community.   To uncover  the  truth  of this  assumption, Sumedang area is selected as  an area that presumably has  the potentials of rituals culture    which  still alive  today.  In the  midst  of today's socio-cultural changes with a mind set oriented on logical and objective thinking, in Sumedang society,   there are still some arts  oriented on non-logical and subjective thinking  such as  the arts  that  serves  as a means  of rituals. Associated with the existence of these arts,  through ethnograp hic studies it will   be   revealed   the   historical   background  of   belief  system   in   the Sumed ang  society,  rituals  performing arts   in  the  Sumedang community, and the types of today's arts used for ritual performances.